“I Have Never Touched It”: Flouting and Violation of Maxims in a Court Testimony - Dito Prasetyo (Passage, 2018)
The present study examines the flouting and violation of maxims in a defendant’s court testimony. It also investigates the possible reasons for flouting and violation of maxims committed by the defendant. As a descriptive qualitative study, the data of the present study are in the form of transcripts of a defendant’s full testimony in the session 26 regarding the court of Olivier café murder case. By employing Grice’s (1975) theory of Cooperative Principle, the findings show that the defendant flouts the maxims of quality, quantity, relation, and manner. It is also found that the defendant only violates the maxim of quality. This present study also discovers that the reason to why the defendant flouts the maxims is generally to build a public image that she is innocent. Furthermore, the defendant violates the maxim of quality because of the intention to get a lesser sentence in the court. The findings suggest that the defendant of the court tends to flout and violate the maxims in giving her testimony to yield hidden additional meanings and intentions in her utterances as well as to mislead her audiences. Keywords: Cooperative Principle, maxims, flouting, violation, court testimony